The Policy of Operational Procedures of Agri Product Marketers Recruitment and Training in PT. Asuransi Jasa Indonesia (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
This research aims to analyze important and necessary components in the SOP development and to formulate the development in the agri recruitment and product marketers training procedures in PT. Asuransi Jasa Indonesia Company. This research type is descriptive research with qualitative approach. The objects in this research are agri recruitment and product marketers training procedures in PT. Asuransi Jasa Indonesia Company. Meanwhile, the subject of this research is human resource department of PT. Asuransi Jasa Indonesia Company. The data collection methods consist of interviews, observations and documentations. Data sources consist of primary and secondary data. The data analysis technique used is SWOT and ISM analysis. The research results showed that the obtained SWOT strategy alternatives are (1) maintaining both external and internal procedures because both recruitment and training models selected in the recruitment and training are very important to recruit the total of prospective employees needed by the company, (2) optimizing company’s resources namely fund readiness and HR, and (3) having a conducive work environment to improve the performance in recruiting prospective employees. From 6 factors of Human Resource Needs, the classification of sub-elements that fulfilled the entry requirement of 4 sectors, of which 6 factors are divided into all sectors. Where sector 1 (Autonomous) has 1 factor namely (1) Strategic Planning and Operation Planning namely in predicting the HR needs. From 6 factors of Main Obstacles, the classification of sub-elements that fulfilled the entry requirement of 4 sectors, of which 6 factors are divided into all sectors. Where sector 1 (Autonomous) has 2 factors namely (1) Underestimating the HR Training, Taking the time to provide on-the-job training to employees is one of the form of investments which definitely will be valuable for the company and (2) Insufficient HR Policy, underestimating the importance of HR audit in company internal scale. From 6 factors of Possible Changes, the classification of sub-elements that fulfilled the entry requirement of 4 sectors, of which 6 factors are divided into all sectors. Where sector 1 (Autonomous) has 1 factor namely (1) Aligning All Processes to Support and Empower Change by carrying out work culture change followed by work ethic.Keywords— SOP Development, Recruitment, Training, Product Marketers.